Sport, exercise and social theory an introduction - Molnar, Gyozo; Kelly, John (Routledge/Taylor & Francis Group, 2013)
It is impossible to properly understand the role that sport and exercise play in contemporary society without knowing a little social theory. It is social theory that provides the vocabulary for our study of society, that helps us ask the right critical questions, and that encourages us to look for the [real] story behind sport and exercise. Sport, Exercise and Social Theory is a concise and engaging introduction to the key theories that underpin the study of sport, exercise and society, including feminism, post-modernism, [Neo-] Marxism and the sociological imagination. Using vivid examples and descriptions of sport-related events and exercise practices, the book explains why social theories are important as well as how to use them, giving students the tools to navigate with confidence through any course in the sociology of sport and exercise. This book shows how theory can be used to debunk many of our traditional assumptions about sport and exercise and how they can be a useful window through which to observe wider society. Designed to be used by students who have never studied sociology before, and including an entire chapter on the practical application of social theory to their own study, it provides training in critical thinking and helps students to develop intellectual skills that will serve them throughout their professional and personal lives.